Islamic Fintech and Financial Inclusion: Innovations for Sustainable Economic Empowerment - Ismamudi Ismamudi; Gina B. Alcoriza; Marzuki Marzuki; Maesya’ Bani (DEAL: International Journal of Economics and Business, 2023)
The rapid growth of financial technology (fintech) has had a significant impact on the global financial sector. In the context of Islamic economics, Shariah-compliant fintech can be an innovative tool to promote sustainable financial inclusion. This paper aims to analyze the role of Islamic fintech in improving access to financial services from an Islamic economic perspective. The research methods used include an in-depth literature analysis of the concept of financial inclusion in Islam, an exploration of various existing Islamic fintech services, as well as successful case studies that reflect the implementation of this concept in society. Through this approach, this paper explains how Islamic fintech can provide solutions to financial access challenges in underserved communities. The analysis shows that Islamic fintech can provide access to a wider range of financial services and empower individuals and micro businesses. Concrete examples of services such as Islamic digital payment services and Islamic peer-to-peer lending show a positive impact in supporting financial inclusion and economic growth in various communities. However, the challenges in the form of complex regulations and the public trust that needs to be built should not be overlooked. This paper also analyzes the opportunities and challenges faced by Islamic fintech in creating a sustainable financial inclusion ecosystem that is in line with Shariah principles. In conclusion, the paper underlines the great potential of Islamic fintech as an innovative tool to achieve better financial inclusion in the Islamic economy. Policy recommendations and further implications are also discussed to ensure the sustainable development of Islamic fintech and its wider positive impact.